2022
DOI: 10.1111/rda.14306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exogenous GnRH administration on lambing performance of oestrus‐synchronized Kazak ewes during the breeding season

Abstract: GnRH given 24 to 36 h after removal of the progestagen pessary synchronizes the luteinizing hormone peak approximately 40 h after pessary removal and ovulation occurs in 90% of ewes within 72 h after pessary removal (Menchaca & Rubianes, 2004). Although GnRH is already widely used in ovine fixed time artificial insemination programmes (Hameed et al., 2021), the effects of GnRH on pregnancy rates are controversial (Menchaca & Rubianes, 2004). Some studies reported that a single dose of GnRH given 24 to 48 h aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…This molecule can also be used to induce estrus synchronization ( 12 , 13 , 16 ). However, we previously found that using GnRH in sheep fixed-time artificial insemination and embryo transfer programs does not increase the embryo and embryo transfer programs decreased the embryo implantation rate ( 17 ). Unfortunately, the mechanism of its negative effect is still unclear.…”
Section: Introductionmentioning
confidence: 97%
“…This molecule can also be used to induce estrus synchronization ( 12 , 13 , 16 ). However, we previously found that using GnRH in sheep fixed-time artificial insemination and embryo transfer programs does not increase the embryo and embryo transfer programs decreased the embryo implantation rate ( 17 ). Unfortunately, the mechanism of its negative effect is still unclear.…”
Section: Introductionmentioning
confidence: 97%